The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1149/1.2779377
|View full text |Cite
|
Sign up to set email alerts
|

All-Wet Strip Approaches for Post-Etch Photoresist Layers After Low-K Patterning

Abstract: Wet-only removal of post-etch (meth-)acrylate based photoresist on porous low-k dielectrics applied in either resist or metal hard mask based patterning is investigated. Characterization of photoresist degradation by etch is applied to support the selection of wet cleaning chemistries and/or cleaning processes. FTIR and 1H-NMR analysis results indicate a common degradation mechanism for both patterning schemes with formation of double carbon bonds in a cross-linked crust that is insoluble in organic solvents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…One reason why the TD brushes stretched less laterally is because of the damage done by RIE to the chains at the very edge of the pattern. Another possibility is the cross-linking between the polymer chains, which could also happen because of RIE treatment. Cross-linking could also explain why the 225 nm pattern relaxed incompletely in acetone. Although cross-linking was not obvious for PMMA brushes, it would later be more obvious for the patterned PMETAC brushes.…”
Section: Resultsmentioning
confidence: 99%
“…One reason why the TD brushes stretched less laterally is because of the damage done by RIE to the chains at the very edge of the pattern. Another possibility is the cross-linking between the polymer chains, which could also happen because of RIE treatment. Cross-linking could also explain why the 225 nm pattern relaxed incompletely in acetone. Although cross-linking was not obvious for PMMA brushes, it would later be more obvious for the patterned PMETAC brushes.…”
Section: Resultsmentioning
confidence: 99%
“…Because such phenomena were not observable for BU patterned brushes, it must be caused by the TD patterning process. A possible explanation for this behavior is that the plasma process induces cross-linking of the polymer at the edges of the pattern through formation of additional covalent bonds. Such cross-linked fraction of the pattern show a rubber-like behavior; i.e., when they are deformed and the forces which cause them to deform are removed, they will return to their original shape. Thus, strong swelling of the system will cause the system to deform, and this deformation is “frozen in” by drying.…”
Section: Resultsmentioning
confidence: 99%
“…1 2 pitch ≤ 90 nm. 6 In previous studies, we have shown that the degradation of 193 nm DUV PR by etch plasma extended much deeper than ion penetration depth and that bulk mod-ifications were comparable to the degradation of PMMA under low energy radiation such as UV. 23,24 The role of plasma Vacuum Ulta Violet (VUV) in deep modifications was confirmed by several dedicated studies.…”
mentioning
confidence: 88%
“…[1][2][3][4] To minimize damage to low-k material, wet alternative methods for removal of PR layer are gaining a renewed interest. [5][6][7][8] Relying on a long tradition of development of solvent based strippers, chemical companies developed a new generation of organic wet strippers targeting the new challenges. [9][10][11][12][13][14] The most widely-used commercially available organic strippers used to be the phenol-based ones, but their short pot life and difficulties with phenol disposal made phenol free strippers, e.g.…”
mentioning
confidence: 99%